PENGARUH PROFITABILITAS, KEPEMILIKAN INSTITUSIONAL DAN SALES GROWTH TERHADAP AGRESIVITAS PAJAK PERUSAHAAN PROPERTI DI BEI - Sari, Azma Fatmaliani; Rasidah, Rasidah (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2025)
The high prevalence of tax aggressiveness practices is one of the factors causing Indonesia’s tax ratio to remain below the ideal standard, reflecting the low effectiveness of tax revenue. Therefore, this study examines the impact of profitability, institutional ownership, and sales growth on tax aggressiveness. Profitability, institutional ownership, and sales growth serve as independent variables, while tax aggressiveness is measured through a proxy known as the Cash Effective Tax Rate (CETR), which acts as the dependent variable. The research objects comprise companies officially listed on the Indonesia Stock Exchange (IDX) within the time frame of 2021 to 2023 in the property and real estate sector. A purposive sampling method was employed based on predetermined criteria, resulting in a sample of 35 companies over the three-year period, yielding a total of 105 samples. Secondary data were utilized, sourced from the annual reports of the companies obtained from the website www.idx.co.id and the respective companies official websites. Data analysis was conducted using multiple linear regression, facilitated by SPSS version 26. The findings of this study reveral that profitability has a significant effect on tax aggressiveness. In contrast, institutional ownership and sales growth show no significant effect on tax aggressiveness.